Lightweight and Mechanically Robust EPDM Foams for High Thermal Insulation and Moderate Ablative Resistance Via Constructing Cellular Char Layer. Issue 2 (5th December 2021) - Qu, Hongjian; Hui, Kun; Bian, Cheng; Guan, Yiwen; Li, Hongyan; Luan, Tao; Yan, Ning
Abstract: Ethylene propylene diene monomer (EPDM) foams have received considerable attention owing to their low weight, low thermal conductivity, and mechanical flexibility. However, their poor ablative resistance and low thermal stability make their use in severe conditions, such as the combustion chamber of a solid rocket motor, difficult. In this study, EPDM foams reinforced with aramid fibers (AFs) and carbon fibers (CFs) are prepared through a hot‐pressing‐induced foaming process. The effects of the fibers on the cellular structure, thermal stability, and mechanical, ablating, and insulating properties of the EPDM foams are investigated. The results show that the addition of CFs enhanced the thermal stability and mechanical properties of the EPDM foams, whereas the use of AFs lowered the thermal conductivity and ablation rate. In particular, when 2.5 phr (parts per hundred parts of rubber) AF and 2.5 phr CF are added, the linear ablation rate tested using oxyacetylene is 0.33 mm s −1, and the back‐face temperature is 53 °C, revealing a good balance in terms of ablative resistance and thermal insulation. Thus, the hybrid‐fiber‐reinforced EPDM foams possess several advantages, such as low weight, good thermal insulation, ablative resistance, and mechanical robustness, suggesting considerable potential for application in the aerospace industry. Abstract : The char layer of A2.5C2.5 presents combined characteristics of single fiber‐filled char layers. Compared with A0C5, the regularity of pores in the char layer of A2.5C2.5 reduces, while the porous structure is densified. Such denser porous structure is more effective to hinder the heat flow erosion than A0C5, and is more conducive to the improvement of thermal insulation than A5C0.